Burnout of special education teachers in Saudi Arabia’s inclusive education schools - Alahmed, Thamer (Frontiers in Education, 2024)
IntroductionBurnout is a serious phenomenon that negatively affects teachers’ professional performance. The current study aims to determine the level of burnout among special education teachers in inclusive education schools in the Kingdom of Saudi Arabia.MethodsIt used a descriptive survey approach by employing an online questionnaire to collect data from 137 special education teachers in inclusive education schools.Results and discussionThe study found that the level of burnout among special education teachers was average, with an arithmetic mean of 2.907 and a relative weight of 48.40%. Male teachers had higher levels of burnout than female teachers. Moreover, teachers specialising in deafness and hearing loss had higher levels of burnout than teachers in other subspecialties. The other variables, such as educational level and experience, had no significant effect on the dimensions of burnout or overall level of burnout. This study recommends the provision of intervention programmes to help reduce teachers’ burnout levels. In addition, there is a need to reduce the workload and tasks assigned to special education teachers in inclusive education schools.